OPTIMASI WAKTU DAN BIAYA PADA PEMBANGUNAN RUMAH SAKIT BRONDONG - LAMONGAN - Suryadi, Muhammad Wahyu Suryadi; Antonius, Antonius; Wibowo, Kartono (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
Delays in project work can be anticipated by accelerating its implementation, but must still pay attention to cost and quality factors. The delay will certainly have an impact on increasing costs, so that additional costs incurred must be optimized so that they can be minimized and still pay attention to quality standards. The implementation of the construction of the Brondong House - Lamongan includes the construction of a two-story building using the Lamongan Regency APBD. Completion of the construction is expected to be completed on time with an implementation time of 150 (one hundred and fifty) calendar days or 3 months. This study aims to analyze the time and cost of the project using the crashing method with the addition of labor, the overlapping method, and a combined method between crashing with the addition of labor and overlapping, with the aim of analyzing the most optimal time and cost using the crashing, overlapping, and overlapping, crashing alternatives. The data needed in this study are in the form of S-curve data and time schedules, weekly project reports, Budget Plans (RAB). Then a discussion is carried out to determine the time and cost due to acceleration with the addition of labor, overlapping, and a combination of overlapping crashing. The acceleration calculation of the three alternatives can be concluded that the optimal time and cost due to acceleration is by using the combined method of crashing, adding labor and overlapping, obtaining a cost reduction of Rp. 291,484,666.67 from the total normal work cost of Rp. 25,313,105,854.21 to Rp. 25,021,621,187.54 or down 1.152% from the total normal work cost with a reduction in work duration of 49 days from the normal duration of 150 days to 101 days.